2018
DOI: 10.5897/jen2018.0208
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Leaf miner (Tuta absoluta) (Meyrick 1917) (Lepidoptera: Gelechiidae) prevalence and farmer management practices in Kirinyanga County, Kenya

Abstract: Pest invasion is one of the limiting factors affecting food production. Tomato leaf miner (Tuta absoluta) (Meyrick 1917) (Lepidoptera: Gelechiidae), is an invasive insect pest of tomato. However, In Kenya, there is limited information on the level of invasion of the pest in tomato producing areas in the country. We assessed the level of invasion of T. absoluta and farmer management practices in Kirinyaga County. Tomato farmers were interviewed using questionnaires aimed at identifying the management practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…is was linked to the product usage abuse, when on-farm interviews were taken where farmers used the insecticide more often than the prescribed manucturer's application rate of a maximum of two applications per crop per year. ese findings are similar to previous study findings where farmers in Kirinyaga consistently use coragen ® chlorantraniliprole to control T. absoluta, and this may accelerate resistance development of the insect pest [28].…”
Section: Interaction Of Host Plant Resistance and Insecticidessupporting
confidence: 90%
See 1 more Smart Citation
“…is was linked to the product usage abuse, when on-farm interviews were taken where farmers used the insecticide more often than the prescribed manucturer's application rate of a maximum of two applications per crop per year. ese findings are similar to previous study findings where farmers in Kirinyaga consistently use coragen ® chlorantraniliprole to control T. absoluta, and this may accelerate resistance development of the insect pest [28].…”
Section: Interaction Of Host Plant Resistance and Insecticidessupporting
confidence: 90%
“…e experimental unit was made up of 16 buckets with a total of 288 buckets for the whole experiment. e treatments included Advances in Agriculture absoluta in Kirinyaga County [28]. Tuta absoluta introduction was performed two weeks after transplanting, and the populations were allowed to establish for two weeks before insecticide application.…”
Section: Experimental Procedurementioning
confidence: 99%
“…Low abundance of natural enemies could also be due to adverse farming practices adopted by growers such as calendar-scheduled applications of pesticides to control T. absoluta and other tomato pests. Indeed, Nderitu et al (2018) observed that farmers in Kirinyaga County sprayed up to 16 times per growing season, which had adverse effects on natural enemies. Awareness campaigns, therefore, on the need to conserve native natural enemies should be considered, because in addition to reducing environmental damage and human health risks, fortuitous biological control could provide some huge economic benefits to growers.…”
Section: Discussionmentioning
confidence: 99%
“…The current control practices for T. absoluta in tomato production systems in Kenya are limited to routine application of synthetic insecticides just like in the native and other invaded regions (Zappalà et al, 2013;Mansour et al, 2018;Nderitu et al, 2018). The larvae, however, escape this approach due to their leaf-mining behaviour (Luna et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation